The relationship between environmental scanning and organizational resilience: Roles of process innovation and environmental uncertainty - YahiaMarzouk, Yasmine; Jin, Jiafei (Frontiers in Environmental Science, 2022)
Due to increased global environment volatility and uncertainty, organizations are constantly faced with unexpected events such as the COVID-19 pandemic, which has brought large international disruptions for several firms. Organizational resilience is a potential notion for describing how firms might stay alive and thrive in such a volatile environment. Therefore, this study aimed to examine how SMEs can foster their resilience through investigating the roles of environmental scanning and process innovation while testing the moderating role of environmental uncertainty. To achieve this aim, we tested a structural model through an empirical investigation with partial least squares structural equation modelling (PLS-SEM) using a sample of 249 Egyptian SMEs. The results reveal that process innovation is a necessary condition for environmental scanning to affect organizational resilience. Furthermore, the results do not support the moderating role of environmental uncertainty the indirect relationship between environmental scanning and organizational resilience. Our findings contribute to innovation and resilience literature by proving that process innovation is a necessary mechanism to translate environmental scanning information to enhance resilience. This research is the first to highlight the role of process innovation in linking environmental scanning to organizational resilience. Our results provide insights about how Egyptian SMEs could remain resilient amidst the COVID-19 through scanning their environments to improve internal processes. We discuss related theoretical and managerial implications.